Merapi (Mengaji Rutin Jam Sepuluh Pagi) as an Assistance Reading Al Qur'an for Housewives at Sidomulyo Village - Yuliani Yuliani; Muslimah Muslimah (CV. Creative Tugu Pena, 2022)
Today's social environment were many problems; the weak ability on reading Al Qur’an. This article gave an assistance of reading Al Qur’an, namely Merapi (Mengaji Rutin Jam Sepluh Pagi) Program for community in assisting housewives at Tumbang Tahai, Sidomulyo Village. This community service program activity used ABCD (Asset Based Community Development) as an approach in empowering assets in the community, namely having human resources who can read the Qur'an properly and correctly and have the time and opportunity to learn to read the Qur'an together. This community service program activity was conducted by students in providing learning experiences to live in the community outside the campus, which directly together with the community identify potentials and deal with problems. It expected to be able to develop village or regional potential and gather social issues for problems that arise. The result showed that the community service program activity, especially the Merapi Program could improve the quality of reading the Qur'an properly and correctly of housewives at Tumbang Tahai, Sidomulyo Village Palangka Raya City. Keywords: Assistance Reading Al Qur’an, Community Service Program, Reading Al Qur’an Program